Nursing students' knowledge, attitudes and awareness regarding shelter nursing in disaster preparedness - Eren, Beytullah; Aktura, Seher cevik; Colak, Mehmet Emin (Bmc, 2025)
BackgroundShelter nursing plays a crucial role in disaster preparedness, yet its integration into nursing education remains limited. This study aims to evaluate nursing students' knowledge, attitudes, and awareness concerning shelter nursing and identify their educational needs in this critical area.MethodsA descriptive cross-sectional study was conducted among nursing students from F & imath;rat University and Sakarya University Faculties of Health Sciences between August and November 2024. A total of 1,450 students were invited, and a sample size of 304 was determined using OpenEpi Version-3 software (power = 80%, confidence level = 95%). Data were collected through an online structured questionnaire, and statistical analyses included descriptive statistics, chi-square tests, means, and standard deviations.ResultsThe study sample included 304 participants with a mean age of 20.92 +/- 2.66 years. The majority were female (83.2%) and single (98.7%). Only 5.9% had prior knowledge of shelter nursing, and 6.6% could correctly define the concept, highlighting significant educational gaps. Chi-square analysis revealed that gender significantly influenced awareness (p = 0.018), with female students demonstrating higher awareness levels. However, no significant differences were observed for other variables. A total of 76.6% of participants identified the need for additional training, while only 1% had received prior education on shelter nursing. Additionally, 91.1% of students reported inadequate knowledge of basic medical interventions in shelter nursing. Despite these gaps, 73.7% expressed a strong interest in crisis management training, with trauma and psychological issues being identified as the most critical health challenges in shelter environments.ConclusionsThere is a critical need to integrate shelter nursing education into nursing curricula to enhance disaster preparedness. Findings highlight the importance of incorporating gender-sensitive and subgroup-focused educational strategies. The inclusion of simulation-based training, field exercises, and disaster management modules is strongly recommended. Although knowledge deficits exist, students' high willingness to engage in shelter nursing education suggests a strong foundation for future curriculum development.Clinical trial numberNot applicable.
Keywords: Disaster management; Disaster preparedness; Nursing education; Shelter nursing; Nursing students